KAJIAN SISTEM DRAINASE KAWASAN PUSAT PERKANTORAN BUKIT PELANGI SANGATTA - IRFAN, ALI (KURVA S JURNAL MAHASISWA, 2014)
Flooding problems in the Sangatta city, especially in the central offices of the rainbowhill that occur almost every year in the rainy season of concern that need to be addressed. Thisthesis to analyze the ability of the existing drainage channel (actual) to accommodate surfacerunoff and stream flow, condition, shape, construction and the direction of the flow channel inthe area of the floodwaters. Boundary problem in terms of this thesis is a hydrological analysis toanalyze rainfall plans, rainfall intensity and time of concentration, while the analysis ofhydraulics to analyze the ability of existing channels (actual) at a location to be review, namelythe central office of Rainbow Hill Sangatta to accommodate runoff and stream discharge.The method used of data collection and analysis. The data used are primary data andsecondary data are then analyzed based on the analysis of hydrology and hydraulics analysis andevaluated based on the actual of the discharge channel with discharge plan.To determine rainfall plans to use two types of distributions are widely used in the fieldsof hydrology, distribution Log Person III and Gumbel distribution, then take of rainfall over theplan period 2, 5, 10, 25 years. Flood discharge plan is calculated using Rational method andNakayasu Synthetic unit hydrograph method.From the calculation of flood discharge on the actual channel with the largest channeldimensions b = 0.65 m and h = 0.70 m when compared with the discharge plan flood returnperiod of 25 years there are some channels that don’t meet so necessary to change thedimensions of the channel becomes b = 0.8 m and h = 1 m.